Oral Literature in Africa - Finnegan, Ruth (World Oral Literature Series, 2012)
Ruth Finneganâ s Oral Literature in Africa was first published in 1970, and since then has been widely praised as one of the most important books in its field. Based on years of fieldwork, the study traces the history of storytelling across the continent of Africa. This revised edition makes Finneganâ s ground-breaking research available to the next generation of scholars. It includes a new introduction, additional images and an updated bibliography, as well as its original chapters on poetry, prose, "drum language" and drama, and an overview of the social, linguistic and historical background of oral literature in Africa. Oral Literature in Africa has been accessed by hundreds of readers in over 60 different countries, including Ethiopia, Kenya, Rwanda and numerous other African countries. The digital editions of this book are free to download thanks to the generous support of interested readers and organisations, who made donations using the crowd-funding website Unglue.it. Oral Literature in Africa is part of our World Oral Literature Series in conjunction with the World Oral Literature Project.